Pengaruh Permintaan Kendaraan Bermotor Terhadap Volume Penjualan Selama Masa Pandemi Pada Dealer Raya Motor Sukses di Kabupaten Enrekang - Muhammad Fahrul Ridwan (Amsir Management Journal, 2022)
This study aims to determine the influence of motor vehicle demand on Raya Motor Sukses dealers during the pandemic. The data collection techniques used in this study are observation, interviews, and literature studies. While the data analysis technique used is an elasticity analysis technique. The results of this study showed that price changes affect changes in motorcycle demand with different percentage changes. For the results of elasticity of demand obtained the result that the value of the coefficient of change starts at the lowest, which is 5.33% and the highest is 99.43%, which is elastic due to the change in the coefficient value > 1%. This means that demand changes with a percentage that exceeds the percentage of price changes. So that it has a positive impact on the sales volume of yamaha motorcycles at the Enrekang Successful Motorcycle Highway Dealer.